Impact assessment of industrialization on the water quality status of river Sirsa situated in the Shiwalik foothills of North Western Himalayas - BHARDWAJ, S. K.; SHARMA, REETIKA (Journal of Soil and Water Conservation, 2019)
The present investigation was carried out to assess the impact of industrial activities on water quality of Sirsa river located in Solan district of Himachal Pradesh. Water quality index (WQI) to depict the overall water quality considering the composite influence of different water quality parameters was also calculated. Significant variations were found in physico-chemical and biological parameters wherein pH, turbidity, EC, TDS, TH, COD, Ca2+, Mg2+, PO4 3-, Cl-, F-, SO4 -, NO3 - and HCO3 - ranged between 6.4-7.5, 79-751, 129-719, 231-1020, 89-305, 65-453, 71-146, 7-45, 0.08-0.72, 55-404, 0.03-19, 34-245, 0.96-12 and 69- 189 mg l-1, respectively. High organic pollution due to various industrial activities was indicated by low DO (0.5-7.5 mg l-1), high BOD (2-62 mg l-1) and TC (120-1800 MPN 100 ml-1) values. Additionally, samples were also observed to contain E. coli ranging from 3.4×103 – 2.6×1011 CFU ml-1 depicting severe faecal contamination. Based on high mean WQI value of 393, maximum of samples was found to be under poor to unfit for drinking category. Interestingly, most of the physico-chemical and biological properties exhibited strong positive correlation by corresponding increase in their concentrations. The findings of the study will help in identifying the factors responsible for surface water pollution and also in framing remedial measures for sustainable water resource management.